Az apostol lappangása a 19. században - Margócsy, István (Studia Litteraria, 2024)
The Apostle is the most elusive work of Petőfi and its reception is just as telling as the work itself. The homogenous consensus on Petőfi’s poetry was challenged by The Apostle as it is significantly different from the rest of the oeuvre both in terms of content and poetics. That is why this work was underrated or simply was not mentioned in the early reception; later it was merely interpreted as an ideological and poetical statement without taking into consideration the poetic inventions of the text. Moreover, the whole text was published 25 years after it had been written, therefore it could not be integrated into the image of Petőfi. This paper focuses on the presence of the text in the hidden canon of the 19th century, emphasizing that the influential folk-national style could not have come into existence without recognising The Apostle: the text (could have) had the potential of an alternative canonical development because of its irregularities and the obvious ignorance of the categories ’folk’ and ’national’.